ISOLASI DAN SELEKSIJAMUR APHYLLOPHORALES PENGURAI LIGNIN DIHUTAN BUKIT BANGKIRAI, KALIMANTAN TIMUR - Subowo, YB (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Isolation and selection of Aphyllophorales as lignin degrading fiingus had been done in Bukit Bangkirai Forest, East Kalimantan. Aim of the research was to obtain Aphyllophorales fungi which have ability to degrade lignin. The fresh fruit bodies were collected from trunks, branches and litters of plants in the forest. The work was conducted at dry season. Fruit bodies were taken to base camp for isolation. The isolates were tested for their ability to degrade lignin. We found 24 isolates of Aphyllophorales fungi. Those isolates were grew in poly R-478 medium, 12 isolates were able to degrade lignin. Megasproporia sp. strain IB-24 had the highest ability in lignin degradation. The fungus can degrade poly R-478 8,05% during 90 minutes.